2014
DOI: 10.1111/1574-6968.12544
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of bacteria via photosensitization of vitamin K3 by UV-A light

Abstract: This study investigated inactivation of bacteria with ultraviolet light A irradiation in combination with vitamin K3 as a photosensitizer. Six bacteria including Bacillus cereus, Pseudomonas aeruginosa, Staphylococcus aureus, Staphylococcus epidermidis, Klebsiella pneumoniae, and Escherichia coli suspended in vitamin K3 aqueous solution were exposed to ultraviolet light A. Five of six bacteria, with the exception of Pseudomonas aeruginosa, were reduced by eight logs with 1600 μM of vitamin K3 and 5.8 J cm(-2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…The UVA photosensitizer application appears to be an attractive approach for whole blood since it has already proved to be successful in platelet and plasma pathogen reduction. We have previously shown that the UVA/VK5 combination, as well as combinations of other vitamins with UVA light, can produce a reduction of bacteria in suspension 6,8 5,7 Our current results show that VK5 and UVA photodynamic treatment can also reduce viral titers in human plasma thus expanding the pathogen reduction potential of this combination.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The UVA photosensitizer application appears to be an attractive approach for whole blood since it has already proved to be successful in platelet and plasma pathogen reduction. We have previously shown that the UVA/VK5 combination, as well as combinations of other vitamins with UVA light, can produce a reduction of bacteria in suspension 6,8 5,7 Our current results show that VK5 and UVA photodynamic treatment can also reduce viral titers in human plasma thus expanding the pathogen reduction potential of this combination.…”
Section: Discussionmentioning
confidence: 51%
“…The plate was sealed with parafilm and shaken at a speed of 50 rpm/min while being exposed at room temperature to UVA irradiation of 0, 35, 70, and 140 J/cm 2 . The energy dose delivered was normalized as the unit of J/cm 2 (approximately 3 min and 20 s per J/cm 2 ) as previously described 6 . All experiments were performed in triplicate or more.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, VitK3 has been reported to induce apoptosis and inhibit the growth of tumor cells, 12,13 which suggests its involvement in oxidative stress. Bergeron et al, 14 reported that VitK3 could be used as a radiosensitizer for hypoxic tumors, whereas Xu et al 15 reported that VitK3 could be used as a photosensitizer. Therefore, the aim of this study was to determine the effect of VitK3 as a potential photosensitizer combined with UVB on apoptosis of cutaneous squamous cell carcinoma A431 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Energy transfer from the electrons can also be directed against molecular oxygen to create highly reactive singlet oxygen ( 1 O 2 ) through Type II reactions 12,19 . All photosensitizers we used in this study can participate in Type I and II reactions and are capable of generating reactive molecules that can cause microbial damage 18,20,21 . Absorption of UV light can alter the photosensitizers as is evident with a change in absorption spectra of some molecules we used.…”
Section: Discussionmentioning
confidence: 99%